Improved generalized transducing bacteriophage for Caulobacter crescentus. - Bender, R A (1981)
Caulobacter phage phi Cr30T, a temperature-sensitive derivative of the lytic, generalized transducing phage phi Cr30, was isolated as a double temperature-sensitive recombinant in a cross between phi Cr30ts1 and phi Cr30ts2, phi Cr30T mediated generalized transduction of Caulobacter crescentus at frequencies comparable to those of phi Cr30 and eliminated the requirement for irradiation of transducing lysates to prevent killing of transductants on the plate.